Do activist hedge funds target female CEOs? The role of CEO gender in hedge fund activism - Francis, Bill B.; Hasan, Iftekhar; Shen, Yinjie (Victor); Wu, Qiang (Journal of Financial Economics, 2021)
Using a comprehensive US hedge fund activism dataset from 2003 to 2018, we find that activist hedge funds are about 52% more likely to target firms with female CEOs compared to firms with male CEOs. We find that firm fundamentals, the existence of a “glass cliff,” gender discrimination bias, and hedge fund activists’ inherent characteristics do not explain the observed gender effect. We also find that the transformational leadership style of female CEOs is a plausible explanation for this gender effect: instead of being self-defensive, female CEOs are more likely to communicate and cooperate with hedge fund activists to achieve intervention goals. Finally, we find that female-led targets experience greater increases in market and operational performance subsequent to hedge fund targeting.